Russia-China Energy Dialogue: Research of the Most Promising Energy Areas for Interrelation - Nezhnikova, Ekaterina; Papelniuk, Oksana; Gorokhova, Anna Evgenievna (International Journal of Energy Economics and Policy, 2018)
Cooperation in the energy sector is an important component of the Russian-Chinese strategic partnership. The purpose of this work is to study the current state and prospects for the development of cooperation in the energy area of Russia and China. The information base of the research is a certain historical material on energy cooperation in the form of a dialogue between Russia and China. The research is based on the principles of a system approach by using historical research methods, comparative and statistical analysis. The results of analyzing the indicators that characterize the effectiveness of the interrelation between the two countries in the energy area allow the author to make the following conclusions. In the context of the complicating geopolitical situation, Russia as the largest exporter of energy resources and a participant in global energy processes has to develop efficient mechanisms for diversifying export of energy resources and to focus on expanding energy cooperation. China is the largest importer of energy resources in the Asia-Pacific region and the world. It can become a promising partner for Russia to implement ambitious energy projects. There are such top-priority directions for the development of bilateral cooperation in the energy sector as participation in projects on developing the Arctic shelves, infrastructure development and increase in the capacity of the Eastern Siberia – Pacific Ocean export route (ESPO), the launch of a new Power of Siberia pipeline, etc. Keywords: energy resources, cooperation, energy dialogue, export of energy resources, gas and oil sector, nuclear power sector, energy consumption. JEL Classifications: L94, O13